Estetika Sastra Populer dalam Film Remake Aladdin (2019) Produksi Disney - Rizki Eka Putri Alda (PENAOQ: Jurnal Sastra, Budaya dan Pariwisata, 2020)
The movie Aladdin was chosen as an object analysis in this reasearch, purposed to elaborate formulas in the movie. Theories used in this research are Bourdieu's cultural production arena theory and Disney's "princess" film formula. The researcher used qualitative research methods to processe and elaborate the data. The results of this study showed that Aladdin was a popular produc producted by Disney that can be proved by the movie’s income which labeled box office and the movie became one of the top 5 successful remake movie in history. The success of the movie can not be happened without the Disney marceting strategy that knows how to analyze the market demand at time. In the Aladdin movie there was same movie formulas as the other Disney’s but there was showed an atmosphere of feminism on the story too. Like, the actualization of the princess Jasmine, who gives a different image compared to the princess in other Disney films. The characterization of Jafar as a villain is capable eliminate the stigma of an evil character that used to play by female characters.